Timescales of influenza A/H3N2 antibody dynamics - Kucharski,AJ; Lessler,J; Cummings,DAT; Riley,S (PLoS Biology, 2018)
Human immunity influences the evolution and impact of influenza strains. Because individuals are infected with multiple influenza strains during their lifetime, and each virus can generate a cross-reactive antibody response, it is challenging to quantify the processes thatshape observed immune responses or to reliably detect recent infection from serologicalsamples. Using a Bayesian model of antibody dynamics at multiple timescales, we explaincomplex cross-reactive antibody landscapes by inferring participants’ histories of infectionwith serological data from cross-sectional and longitudinal studies of influenza A/H3N2 insouthern China and Vietnam. We find that individual-level influenza antibody profiles canbe explained by a short-lived, broadly cross-reactive response that decays within a yearto leave a smaller long-term response acting against a narrower range of strains. We alsodemonstrate that accounting for dynamic immune responses alongside infection history canprovide a more accurate alternative to traditional definitions of seroconversion for the estimation of infection attack rates. Our work provides a general model for quantifying aspectsof influenza immunity acting at multiple timescales based on contemporary serological dataand suggests a two-armed immune response to influenza infection consistent with competitive dynamics between B cell populations. This approach to analysing multiple timescalesfor antigenic responses could also be applied to other multistrain pathogens such as dengueand related flaviviruses.